1995
DOI: 10.1016/0014-5793(95)00430-h
|View full text |Cite
|
Sign up to set email alerts
|

4‐Hydroxyphenethyl alcohol — a new cytokinin‐like substance from the phototrophic purple bacterium Rhodospirillum rubrum 1R

Abstract: Three compounds with cytokinin activity have been isolated from the medium of Rhodospirillum rubrum grown photosynthetically. Two N-6 aminopurine cytokinins revealed in the medium were identical with those obtained from R. rubrum cells previously. The third compound with cytokinin activity in Amaranthus caudatus bioassay proved to be a simple phenolic compound with elemental composition CsHioO 2. This cytokininlike substance according to absorption spectra, mass spectrometry and IH NMR spectra data was identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…PSU-F14 y PSU-F135, y Nigrospora sphaerica (34)(35)(36). Múltiples actividades biológicas se les han atribuido incluyendo antioxidante e inhibidores de citoquinina (37)(38)(39). El tirosol es una molécula de comunicación utilizada por el hongo Candida albicans favoreciendo por medio de QS el inicio de la filamentación (40)(41)(42) pero no se había descrito actividad inhibitoria del quorum sensing en bacterias aunque si su producción, como es el caso de Bacillus subtilis KMM 3427 (43), aunque compuestos similares (orto-dihidroxilados) han sido patentados recientemente con este fin (44).…”
Section: Discussionunclassified
“…PSU-F14 y PSU-F135, y Nigrospora sphaerica (34)(35)(36). Múltiples actividades biológicas se les han atribuido incluyendo antioxidante e inhibidores de citoquinina (37)(38)(39). El tirosol es una molécula de comunicación utilizada por el hongo Candida albicans favoreciendo por medio de QS el inicio de la filamentación (40)(41)(42) pero no se había descrito actividad inhibitoria del quorum sensing en bacterias aunque si su producción, como es el caso de Bacillus subtilis KMM 3427 (43), aunque compuestos similares (orto-dihidroxilados) han sido patentados recientemente con este fin (44).…”
Section: Discussionunclassified
“…For example, the fungus Alternaria sp. and the bacterium Rhodospirillum rubrum produce previously unknown plant growth regulators altechromone and 4‐hydroxyphenethyl alcohol, respectively (Kimura et al 1992, Serdyuk et al 1995). In this study, it was shown that some bud endophytes of Scots pine produce adenine and adenine derivatives.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokinins were extracted as described by Serdyuk et al (1995). The acidic aqueous solution was adjusted to pH 8 with 2 N NaOH and extracted three times with water‐saturated n ‐butanol.…”
Section: Methodsmentioning
confidence: 99%
“…Cytokinins represent another class of phytohormones produced by micro‐organisms. Their production by plant‐associated microbes, as well as by phototrophic micro‐organisms, has been well documented (Arshad & Frankenberger 1991; Serdyuk et al . 1995), although the endogenous production of cytokinin by plants remains controversial (Holland 1997).…”
Section: How Rhizobacteria Promote Plant Growth: Direct Impact On Plamentioning
confidence: 99%